Modulation by ryanodine of active calcium loading and caffeine induced calcium release of heavy sarcoplasmic reticulum vesicles - Hasselbach, Wilhelm; Migala, Andrea (Zeitschrift für Naturforschung. C, a journal of biosciences, 1992)
The effect of ATP on the calcium release channel in heavy sarcoplasmic reticulum vesicles modulated by ryanodine has been analyzed by monitoring active calcium uptake and caffeine induced calcium release under near physiological conditions. Native as well as ryanodine reacted vesicles display a complex time course of calcium uptake resulting in nearly complete exhaustion of medium calcium when ATP in combination with an ATP-regenerating system, in contrast to ATP alone, or dinitrophenyl phosphate, were used to support calcium uptake. Applying of dinitrophenyl phosphate as energy yielding substrate, not affecting channel activity, allowed to estimate the fraction of light vesicles devoided of calcium channels contam inating the heavy preparation as the fraction that stores calcium after the preparation has been treated with channel opening, low concentrations of ryanodine (1 μᴍ). Calcium uptake by contaminant light vesicles (25%) cannot account for calcium storage, as well as, abolition of caffeine induced calcium release of ryanodine treated heavy vesicles. Calcium uptake of native and ryanodine treated vesicles is accompanied by the uptake of equivalent amounts of inorganic phosphate arising from ATP hydrolysis indicating that calcium is mainly stored as calcium phosphate. The momentary capability of the preparation to accumulate calcium was measured by activating calcium uptake during the calcium storage period with 0.2 mᴍ 45 CaCl 2 and 4 mᴍ phosphate at short time intervals. A significant increase of the momentary uptake activity with time was observed being more pronounced for ryanodine treated than for native vesicles indicating that under regenerating conditions, ATP can induce closing of the native and even more effectively of the ryanodine modified calcium release channels.
Elektronische Reproduktion der Druck-Ausgabe 2. Juni 2014
Gesehen am 21.07.2025